1996
DOI: 10.1007/s002130050130
|View full text |Cite
|
Sign up to set email alerts
|

The effects of early postnatal stimulation on Morris water-maze acquisition in adult mice: genetic and maternal factors

Abstract: Following stressor exposure BALB/cByJ mice exhibit hypersecretion of corticosterone and marked brain catecholamine alterations. In addition, mice of this strain exhibit impairments of performance in a Morris water-maze, which may be exacerbated by footshock application. In the present investigation it was demonstrated that early-life handling of mouse pups (coupled with brief separation periods from the dam over the course of 21 days postpartum) reduced the learning impairments seen when mice were tested in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
99
0
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(114 citation statements)
references
References 33 publications
13
99
0
2
Order By: Relevance
“…These results suggest then that the reason CRFR1-mutant male mice previously reported to display dramatic anxiolytic-like behaviors are now not statistically different from controls is attributable to an effect of their mother's genotype. Previous studies have well defined the nurturing roll of the dam and how this behavior may affect the adult anxiety of the pup, suggesting that a low-nurturing mother leads to a highanxiety pup (Zaharia et al, 1996;Caldji et al, 1998). In addition, studies have also shown that the stress hormone levels of the dam during pregnancy affect the anxiety levels of the pups (Takahashi et al, 1988(Takahashi et al, , 1990(Takahashi et al, , 1992Takahashi and Kalin, 1991;Cratty et al, 1995;Vallee et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest then that the reason CRFR1-mutant male mice previously reported to display dramatic anxiolytic-like behaviors are now not statistically different from controls is attributable to an effect of their mother's genotype. Previous studies have well defined the nurturing roll of the dam and how this behavior may affect the adult anxiety of the pup, suggesting that a low-nurturing mother leads to a highanxiety pup (Zaharia et al, 1996;Caldji et al, 1998). In addition, studies have also shown that the stress hormone levels of the dam during pregnancy affect the anxiety levels of the pups (Takahashi et al, 1988(Takahashi et al, , 1990(Takahashi et al, , 1992Takahashi and Kalin, 1991;Cratty et al, 1995;Vallee et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several recent studies in rats have described the long-term neural as well as behavioral consequences of variations in early social experience. Reduced maternal grooming and licking is associated with significant and persistent differences in the adult offspring's emotionality (Caldji et al, 1998), cognition (Zaharia et al, 1996), hypothalamic CRH, and AVP mRNA expression (Liu et al, 1997), as well as binding to GABA A , CRH, a 2 -adrenergic (Caldji et al, 1998), and glucocorticoid receptors in the brain (Sutanto et al, 1996). Two independent groups have reported a decrease in OT receptor binding in the amygdala, following repeated mother-infant separations or decreased maternal licking and grooming (Francis et al, 2000;Noonan et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…This work has received attention among PTSD researchers because of the parallel findings in humans, which link hypothalamic-pituitary-adrenal axis dysregulation and childhood maltreatment with predisposition to PTSD (Binder et al, 2008;Shea et al, 2005;Yehuda and LeDoux, 2007). Specifically, Meaney's lab has shown that natural variations in maternal licking and grooming alter DNA methylation and the expression of the glucocorticoid receptor gene, and produce altered patterns of hypothalamic-pituitary-adrenal axis reactivity, anxiety, and cognitive function in adulthood (Francis and Meaney, 1999;Liu et al, 2000;Meaney and Szyf, 2005a;Weaver et al, 2002a;Weaver et al, 2002b;Zaharia et al, 1996). These studies implicate epigenetic mechanisms in providing a critical link between early-life environment and sensitivity to stressors in later life, which is critical for developing a complete model of PTSD that integrates pre-existing risk factors with an exaggerated response to trauma in adulthood.…”
Section: Epigenetic Mechanisms In Ptsdmentioning
confidence: 99%